(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The settlement on the admission of guilt is a relatively new legal institution in our criminal procedure law. Not even five years have passed since the entry into force of the relevant regulation, however, the representatives of the profession are still keenly interested in the question of whether the results of the legal application of the agreement justify the legislator’s expectations. The author of this study aims to reflect on some significant critical professional observations from his point of view. Methodology: The author discusses the regulatory history of the legal institution and the legislative intent behind it. It quotes the most important scientific research results. Eventually, it draws conclusions based on statistical indicators. Findings: The low statistical data of the settlement does not give a complete picture to consider this legal institution. According to the author’s point of view, it is not merely a question of quantity but also quality. It can be concluded that, in practice, settlement typically takes place in complex, complicated cases, whose financial and human resources, as well as their social focus, exceed the average. Value: The study sheds light on the issue of how the settlement is judged from a new angle, therefore shading the criticism that this legal instrument did not fulfil the expectations attached to it.